The Urgency of Halal Label in Cosmetics for Muslim Women in Pemalang City - Nanda Nuril Arifa; Hendri Hermawan Adi Nugraha (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
This study focuses on the orientation of the actions of Muslim women in the city of Pemalang towards the selection of cosmetics labeled halal and the meaning that underlies these actions. The method in this study is to use a qualitative method with a phenomenological approach. The findings of this study are Muslim women in Pemalang city are aware of religious values. Halal labels found on cosmetic products with halal labels become a symbolic representation of Islam. There is an externalization process in the form of implications for consumers considering halal-labeled cosmetic products as a form of Islamic symbolic representation. The objectification process is marked by changes in behavior that are even more selective in using cosmetic products, the internalization process with the influence of environmental factors who use cosmetic products labeled halal so that it affects consumer decisions to buy cosmetic products labeled halal. After this perception, people's beliefs and attitudes arise with the existence of a halal label, and in the end these beliefs and attitudes affect people's purchases.